2002
DOI: 10.1159/000063299
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Suppresses Osteopontin Expression and Inflammatory Cell Infiltration in Chronic Cyclosporine Nephrotoxicity

Abstract: Background: Colchicine (Col) is beneficial to renal injury because of its anti-inflammatory effect, but its mechanism has yet to be elucidated. The present study was designed to evaluate the inhibitory effects of colchicine on osteopontin (OPN) expression and the macrophage accumulation in chronic cyclosporine (CsA) nephrotoxicity in rats. Methods: Male adult Sprague-Dawley rats on a low salt diet (LSD, 0.05% sodium) were treated daily with Col (30 µg/kg), CsA (15 mg/kg), and both CsA and colchicine or vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Others and we have demonstrated that overexpression of OPN is closely associated with macrophage infiltration as well as TIF in chronic CsA nephropathy [27, 28, 38]. Furthermore,mice lacking OPN (OPN–/–) showed less chronic CsA nephropathy than OPN wild-type (OPN+/+) mice [39], indicating a role for OPN in chronic CsA nephropathy.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Others and we have demonstrated that overexpression of OPN is closely associated with macrophage infiltration as well as TIF in chronic CsA nephropathy [27, 28, 38]. Furthermore,mice lacking OPN (OPN–/–) showed less chronic CsA nephropathy than OPN wild-type (OPN+/+) mice [39], indicating a role for OPN in chronic CsA nephropathy.…”
Section: Resultsmentioning
confidence: 95%
“…Tubulointerstitial inflammation is critical in the development of chronic CsA nephropathy, and several proinflammatory mediators are involved in this process [11, 27, 28]. In this study, we evaluated infiltration of macrophages and two potential proinflammatory mediators (OPN and CRP) as markers of CsA-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, this study aimed to investigate the effect of losartan on βig-h3 expression and its relation to TIF in a well-established rat model of chronic CsA nephrotoxicity [7, 8, 9, 10, 11, 12, 13, 20, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…Colchicine inhibits lymphocyte proliferation and function [21,22] . In the rat chronic cyclosporine (CsA) nephrotoxicity model, colchicine prevented macrophage influx and renal tubulointerstitial fibrosis [23] . Similarly, colchicine prevented macrophage infil- Experimental and clinical studies of colchicine in the renal disease processes with prominent fibrosis or in fibrotic disorders in which kidney is involved collaterally Reference Study design and setting…”
Section: Colchicine In Renal Fibrosismentioning
confidence: 99%